The fungal genus Tricholomopsis (Agaricales) in New Zealand, including Tricholomopsis scabra sp. nov. - Cooper, Jerry A.; Park, Duckchul (Phytotaxa, 2016)
The status of the genus Tricholomopsis (Agaricales) in New Zealand is reviewed. T. rutilans is a species described from the northern hemisphere and recorded from plantations of exotic Pinus radiata in New Zealand. Historical collections identified as T. rutilans were subjected to morphological and phylogenetic analysis. The results show that most of these collections refer to T. ornaticeps, originally described from New Zealand native forests. The presence in New Zealand of T. rutilans was not confirmed. Collections of Tricholomopsis from native forests and bush also include a newly described species, T. scabra, which is characterised by a distinctly scabrous pileus. The new species is phylogenetically and morphologically distinct but related to T. ornaticeps. T. ornaticeps and T. scabra are currently known only from New Zealand and the former has extended its habitat to include exotic conifer plantations.